Sound Change in The Japanese Numeral Quantifiers - Suhartini Suhartini (Universitas Diponegoro, 2022)
This research deals with the sound change of Japanese numeral quantifiers. The data were collected through introspection method and by asking Japanese native speakers as verifiers. The data were identified in order to investigate which numerals have the potential to undergo some sound change. They were then analyzed phonemically and some phonetically as well. The data analysis focused on the segmental elements and it was conducted synchronically. The results show that there are some processes of and reasons underlying the sound change in the Japanese numeral quantifiers. The most common process of the sound change is assimilation, especially regressive assimilation. Meanwhile, the reasons underlying the sound change are the presence of sound co-articulation, phonotactics in Japanese that prevents any consonant clusters except /QC/ and /NC/, devoicing of high vowel /i/, and to comply with the construction of similar numerals. <a href=